The Effect of Study Balance, Career Balance, and Personal Life Balance on Academic Achievement in Master's and Doctoral Program Students of FEB USU is Mediated by Academic Motivation Plantation - Siti Humaira; Elisabet Siahaan; Parapat Gultom (Journal of Business Management, 2026)
This study aims to analyze the influence of study balance, career balance, and personal life balance on academic achievement in married Master's and Doctoral Program students of the Faculty of Economics and Business, University of North Sumatra (FEB USU), with academic motivation as a mediating variable. The research population is all students of the Master of Management Science Program FEB USU in 2025, which totals 349 students. This study is focused on 141 married students with a sampling technique using total sampling. The research method used is a quantitative approach with the type of associative research. Data were collected through questionnaire distribution and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results of the study showed that study balance had a positive but not significant effect on academic achievement. On the other hand, career balance and personal life balance have a positive and significant effect on academic achievement. These three dimensions of balance have also been shown to have a positive and significant effect on academic motivation. Academic motivation then has a positive and significant effect on academic achievement and is able to mediate the influence of study balance, career balance, and personal life balance on academic achievement. Academic motivation fully mediates the influence of study balance on academic achievement because its direct influence is not significant, but becomes significant through indirect channels.